2007
DOI: 10.1007/s11064-007-9349-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia and Oxidative Stress on Expression of Neprilysin in Human Neuroblastoma Cells and Rat Cortical Neurones and Astrocytes

Abstract: Pathogenesis of Alzheimer's disease (AD), which is characterised by accumulation of extracellular deposits of beta-amyloid peptide (Abeta) in the brain, has recently been linked to vascular disorders such as ischemia and stroke. Abeta is constantly produced in the brain from amyloid precursor protein (APP) through its cleavage by beta- and gamma-secretases and certain Abeta species are toxic for neurones. The brain has an endogenous mechanism of Abeta removal via proteolytic degradation and the zinc metallopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 38 publications
2
69
0
1
Order By: Relevance
“…Here, we measured degradation of exogenous A␤ in SH-SY5Y cells, a human neuroblastoma cell line widely used for A␤ metabolism (19). As expected, exogenous A␤42 was degraded more efficiently (reduced to 36% of input substrate) in cells treated with 17␤-estradiol (100 nM for 24 h).…”
Section: ␤-Estradiol Enhances A␤42 Degradation and Up-regulatesmentioning
confidence: 54%
“…Here, we measured degradation of exogenous A␤ in SH-SY5Y cells, a human neuroblastoma cell line widely used for A␤ metabolism (19). As expected, exogenous A␤42 was degraded more efficiently (reduced to 36% of input substrate) in cells treated with 17␤-estradiol (100 nM for 24 h).…”
Section: ␤-Estradiol Enhances A␤42 Degradation and Up-regulatesmentioning
confidence: 54%
“…Анализируемые пробы добавляли в лунки 96-луночного планшета, в которые предварительно вносили реакционную смесь объемом 100 мкл, состоявшую из 50 мM HEPES буфера, 200 мM NaCl (pH 7,2) и 4 миллиединиц лейцинаминопептидазы (ЛАП, «Sigma»). Активность НЕП определялась по разни-це между флюоресценцией продукта, полученного в ре-зультате инкубации анализируемых проб без и в присут-ствии специфического ингибитора НЕП тиорфана (10 мкМ) [49]. Линейность реакции образования продукта оценивалась с помощью флюориметрии в присутствии избыточных количеств ЛАП, необходимых для создания условий, в которых скорость реакции лимитируется толь-ко присутствием анализируемого НЕП.…”
Section: материал и методыunclassified
“…It has been demonstrated that levels of expression and activity of the main proteases participating in brain Aβ metabolism in vivo, and especially of neprilysin (NEP; CD10), decline markedly with age, under hypoxia or ischemia and are even lower in AD patients (Caccamo et al 2005;Fisk et al 2007;Nalivaeva et al 2004;Wang et al 2010). In this regard, up-regulation of NEP and other amyloid-degrading enzymes is considered as a viable therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%